STRATEGIC MARKETING AND HUMAN SUBJECTIVITY - E.M. PETROVA (Advanced Engineering Research, 2006)
The article analyses the marketing evolution, gives the original approach to marketing definition, emphasizes the significance of strategic, marketing both from the point of simulation of any enterprise future activity and from the point of chosen courses of its activity. The concept of marketing complex is also analyzed. The application of marketing is different fields, creation of new technologies, interactive marketing and the internet allow to enrich the marketing complex with new elements, which extend its application for solving different marketing tasks. The concept of human subjectivity in the context of marketing strategy is presented as well.